Pertumbuhan dan Produksi Tanaman Bawang Merah (Allium ascalonicum L.) dengan Pemberian Kompos Rumen Sapi dan Pupuk NPK - Siti Hardiyanti; Armaini Armaini; Idwar Idwar (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2019)
ABSTRACTThe research aim to examine the effect of interaction of cow rumen compost with NPK fertilizer and single factor of cow rumen compost, NPK fertilizer and get the best treatment combination in increasing the growth and yield of shallot. The research was conducted at UPT (Unit Pelaksanaan Teknis) of Faculty of Agriculture Universitas Riau from September to November 2018. The research was done in a completely randomized design (CRD) factorial and repeated three times. The first treatment was cow rumen compost that consist of 0 kg per plot, 2 kg per plot, 4 kg per plot and 6 kg per plot. The second factor was NPK fertilizer that consist of           0 g per plot, 30 g per plot and 60 g per plot. The observation parameters were relative growth rate, number of leaves per clump, number of tubers per clump, tuber circumference per clump, plant dry weight on day 50, fresh tuber weight per clump and tuber weight worth keeping per clump. The research data were analyzed using analysis of varriance (ANOVA) and followed by duncan’s new multiple range test (DNMRT) at level 5%. The result of the research showed that the treatment of cow rumen compost 6 kg per plot, NPK fertilizer 60 g per plot and the treatment combination of cow rumen compost 6 kg per plot with NPK fertilizer 60 g per plot were the best treatments in increasing 3,9 ton.ha-1 the growth and yield of shallot.Keywords: shallot, growth, yield, cow rumen compost, NPK fertilizer.